The Correlation Between Breakfast Habits and Students’ Learning Concentration of Class VII at SMPN 9 Palangka Raya - Priskila Hutapea; Riska Ovany; Merry Delyka (PROMOTOR, 2026)
Introduction: Breakfast plays a very important role in the fulfillment of nutrition in the morning, more specifically for students who have very busy academic activities. A good concentration is needed in the learning process, because with optimal concentration, students can understand the material more effectively. Seeing the important role of breakfast in learning concentration, evaluative and educational efforts are needed on students' breakfast habits. Objective: To determine the correlation between breakfast habits and students’ learning concentration in class VII at SMPN 9 Palangka Raya. Methods: correlational method with cross-sectional design. The sample in this research was some of the seventh-grade students of SMPN 9 Palangka Raya, totaling 141 students. The sampling technique was proportional random sampling. The data analysis was conducted using Spearman's rank test. Results: Based on the spearman rank test obtained significance results (p-value < 0.05) which was 0.000, it could be concluded that there was a statistically significant correlation between breakfast habits and learning concentration. With a correlation coefficient value of 0.322, which showed this correlation was positive with a weak to moderate correlation strength, which means that the better the students' breakfast habits, the better their learning concentration tends to be. Conclusion: There is a positive correlation between breakfast habits and students' learning concentration. This means that students who have good breakfast habits tend to have better learning concentration. It was recommended that students get into the habit of eating breakfast regularly, especially before going to school.